Fiscal interactions among European countries.: does the EU Matter? - Michela Redoano (Center for Economic Studies and ifo Institute (CESifo), 2007)
We use a panel of European countries to investigate whether or not governments interact with their neighbors when they decide their fiscal policy; we consider both taxes and expenditures, at aggregate and at separate aspects of policy. We analyse possible different competitive behaviours and find evidence of fiscal interdependencies consistently with the literature on tax and yardstick competition. For corporate taxes, the regression results suggest that European countries follow large countries in order to attract capital; for income taxes and public expenditures, instead, fiscal interactions exist but they are mainly due to yardstick competition. Finally, we have found the countries are interdependent with each others before joining the EU, and than, once they are in, they become more independent.
Keywords: H2; H77; H87; D7; 330; Öffentliche Finanzplanung; Steueraufkommen; Steuerwettbewerb; EU-Staaten